1987
DOI: 10.1113/jphysiol.1987.sp016859
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in human vision under bright light: grain or gain?

Abstract: SUMMARY1. The factor by which increment threshold changes with changing background intensity is less if the test flash is small than if it is large. This is commonly attributed to a reduction of the area over which visual signals are integrated as light adaptation increases.2. We propose and test an alternative hypothesis that the change in slope is the result of purely local processes: if it is assumed that increasing the background intensity increases the exponent of the local response function, but does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Similar shifts were found by Chen et al (1987;see their Fig. 8) in two of their four subjects and have been noted by Whittle & Challands (1969).…”
Section: Rod Spatial Integration and Sensitivitysupporting
confidence: 69%
See 4 more Smart Citations
“…Similar shifts were found by Chen et al (1987;see their Fig. 8) in two of their four subjects and have been noted by Whittle & Challands (1969).…”
Section: Rod Spatial Integration and Sensitivitysupporting
confidence: 69%
“…Traditionally, this is attributed to neural spatial reorganization somewhere in the retina; being most frequently related to the increasing prominence with light adaptation of the inhibitory surround in retinal ganglion cells (Barlow, 1958). However, Chen et al (1987) have shown for cone vision, first that there is only a small change in TVI slope caused by changes in test flash size (the slopes of their small and large field increment threshold functions differ by not more than 20%; on average 097 vs. 08) -so that independent of any interpretation the change of spatial integration is less than is usually supposed -and second, that the change in slope can be mostly accounted for by local adaptation changes that involve no alteration in spatial organization with background intensity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations